Comparative Study of Hardiness Referring to Adolescents with Musculoskeletal Disorders and Adolescents with Normal Development - Tokarskaya, L (KnE Life Sciences, 2018)
The article presents the results of the research into hardiness of adolescents with musculoskeletal disorders (MSDs) and those with normal development. The choice of subjects with MSDs was made due to their presence in the general public, in fact, the incidence of inborn and acquired MSDs is about 5-7% in children (N.М. Nazarova, 2002). 25 adolescents with MSDs studying at schools which have adaptive standards of education took part in the research, and 50 adolescents with normal development studying at general education schools. The research used the following methods: modified Maddi’s Hardiness Survey (adapted by D.A. Leontiev, E.I. Rasskazova); H. Eysenck Personality Questionnaire (EPI); Dembo-Rubinstein Method of Self-esteem Measurement (modified by A.M. Prikhozhan); questionnaire ’Ways of Coping Checklist’ (WCC) of R. Lazarus and S. Folkman (adapted by L.I. Wasserman). Such psychological correlates of hardiness as self-esteem, claims, and extroversion - neuroticism, ways of coping, are used to clarify the specificity of hardiness manifestation in test subjects. As the result of the study, the hypothesis that the presence of MSDs will have an influence on the level of hardiness of adolescence was confirmed, as hardiness components are higher in children with MSDs than in those with normal development, 95,5 and 77,6 respectively. Also, the hypothesis that children with MSDs have a high level of neuroticism was confirmed. However, adolescents without MSDs studying at 8th grade have an even higher level of neuroticism, the study finds. Keywords: hardiness, adolescents with MSDs, adolescents with normal development, ways of coping, self esteem, claims, extraversion, neuroticism.